Viral Hepatitis in Hemodialysis: An update - Mahmood, Nazneen; Siddiqui, Md Mahmudur Rahman; Giasuddin, Rubayat Sheik (Anwer Khan Modern Medical College Journal, 2020)
Hepatitis outbreaks in hemodialysis (HD) patients and staff were reported in the late 1960s, and a number of hepatotropic viruses transmitted by blood and other body fluids have been identified. Hepatitis B virus (HBV) was the first significant hepatotropic virus to be identified in HD centers. HBV infection has been effectively controlled by active vaccination, screening of blood donors, the use of erythropoietin and segregation of HBV carriers. Hepatitis delta virus is a defective virus that can only infect HBV-positive individuals. Hepatitis C virus (HCV) is the most significant cause of non-A, non-B hepatitis and is mainly transmitted by blood transfusion. The introduction in 1990 of routine screening of blood donors for HCV contributed significantly to the control of HCV transmission. An effective HCV vaccine remains an unsolved challenge; however, pegylation of interferon-alfa has made it possible to treat HCV-positive dialysis patients. Unexplained sporadic outbreaks of hepatitis by the mid-1990s prompted the discovery of hepatitis G virus, hepatitis GB virus C and the TT virus. The vigilant observation of guidelines on universal precaution and regular virologic testing are the cornerstones of the effective control of chronic hepatitis in the setting of HD. Major recent advances in the viral diagnosis technology and the development of new oral, direct acting antiviral agents (DAAs) allow early diagnosis and better therapeutic response. The current update will review the recent developments, controversies and new treatment of viral hepatitis in HD patients. AKMMC J 2020; 11(2) : 128-136